Comparative assessment of physical activity and sports motivation indicators of physical education university students in Russia and China - Wang E. ,; Zhong T. ,; Li Y. ,; Galysheva S.M. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to conduct a comparative assessment of the level of physical activity and sports motivation of students at physical education universities in Russia and China. Methods and structure of the study. Scientific work was carried out among 223 students of physical education universities: Russian students 96 people (56 women and 40 men), Chinese students 127 people (57 women and 70 men). To achieve the goal, the following were used: a short version of the International Physical Activity Questionnaire (IPAQ), and the “Sports Motivation Scale” questionnaire. The results were analyzed separately among male and female students. Results and conclusions. There are significant differences in the time spent on high-intensity physical activity (p≤0.01) and walking (p≤0.01), these indicators are higher among Russian male students compared to Chinese male students. No significant differences were found among female students. The data obtained indicate a certain difference in the lifestyle of students from different countries and in preferences for types of physical activity. A study of sports motivation proved that it is significantly higher among Chinese students, both men and women (p ≤0.01). The data prove the high role of the cultural factor in the formation of sports motivation of students.